Síntese e caracterização de catalisadores de ZnO, NaX-ZnO, Nd2O3-ZnO e Nb2O5-ZnO para aplicação na fotodegradação da ciprofloxacina - Costa, Sabryna Isabelly Giordani da (2018)
The objective of this research was to synthetize and characterize ZnO based catalysts – pure and non-pure as doped with neodymiun trioxide (Nd2O3), zeolite composite (NaX) and Niobium pentoxide (Nb2O5) and evaluating these materials in Ciprofloxacin Hydrocloride antimicrobial and photocatalytic activity. In order to execute it, ZnO was synthetized by simple precipitation (SP), solochemical (SOL) and homogeneous solution precipitation (PSH). The catalysts were characterized by XRD, SEM-EDSX, Raman, FT-IR, N2 Physisorption, DRS, null charge point and photoluminescence. The photocatalytic activity of these materials by the 33 experimental design, changing the initial concentration of CIP, catalyst concentration and synthesis. After, the non-pure catalysts, doped ZnO with different proportions of Nd2O3 (1, 3 e 5% in mass), composite of NaX and ZnO (0.25:1 e 0.50:1) and composite of Nb2O5 and ZnO (0.25:1 and 0.50:1), were prepared, characterized with the same methodology as the pure ZnO, and evaluated in the photocatalytic degradation of CIP through the Box-Behnken planning. Based on the ZnO characterization analysis, was ascertained that the ZnO showed hexagonal wurtzita phase with crystallite diameter of 24 nm for ZnO via SP and PHS and 27 nm for the SOL, BET area of 8.1, 19.4 and 15.4 m2g-1 for the ZnO via SOL, SP and PSH, respectively, and band gap energy of 3.2 eV. The analyse of Raman proved that all ZnO had a good crystallinity. The ZnO via SP showed particles like pseudo spheres or grains, ZnO via SOL showed particules was morphology was polydisperse, like “needles” or “leaf” and ZnO via PHS showed “flower” structures type. All synthetized materials showed highly efficient in catalyzing CIP, with the degradation above 90% in 150 min. By the analysis of the desirability function, it was concluded that the optimal condition for the degradation of CIP was when ZnO PS was used in the content of 1.9 g L-1 in 5 m L-1 concentration of CIP. By characterization of the doped and composite catalysts, it was verified that all the samples have wurtzite hexagonal structure, characteristic of the ZnO, being also identified diffraction peaks associated to the NaX, Nb2O5 and Nd2O3 phases. The crystallite diameters were 19.45, 19.24, 58.77, 51.08, 24.91, 25.96 and 27.98 nm for the NaX-ZnO 0.5: 1 and 1: 1 catalysts, 0.5:1 and 1:1 Nb2O5 -ZnO, and 1, 3 and 5% Nd2O3 -ZnO, respectively. The band gap energy was higher than that of ZnO (3.39 and 3.36 eV), whereas for the Nb2O5-ZnO composite, independent of the Nb2O5 ratio, the composite NaX-ZnO 0.5:1 and 1:1 was lower (3.15 eV). For the doped catalysts, the band gap energy of Nb2O5-ZnO was 3.23, 3.24 and 3.17 eV for the contents of 1, 3 and 5% of Nd2O3, respectively. The technical Raman proved that mixed samples interfered in the crystallinity of the material, however, they remained with considerable crystallinity.. SEM images revealed that the mixed and doped samples gave different morphologies to the ZnO, however the material remained on a nanometric scale, and the NaX samples showed spherical and porous particles whereas the mixed samples with Nb2O5, pseudospherical agglomerates and samples doped with Nd2O3 showed nanoplates with growth as cauliflower. By means of the photocatalytic tests, it was possible to conclude that all the composites and doped catalysts were efficient in the degradation of CIP, since they showed degradation efficiency superior to 90% after 150 min of degradation. From the Box-Behnken experimental design, it was determined that there was an optimum value for NaX and Nb2O5 ratio and Nd2O3 content. The optimal condition for CIP degradation was when 5 mg L-1 of CIP was used with 1.45 g L-1 of the catalysts 1% Nd2O5 -ZnO, NaX-ZnO 0.5:1 and Nb2O5 -ZnO 1:1. However, 1% Nd2O3-ZnO was the most photoactive catalyst for the photocatalytic degradation of ciprofloxacin, making it a promising nanomaterial for the remediation of effluents with drugs, contributing to the development of sustainable technologies without damaging future generations.